Consensus statement: improvement in care and outcomes for patients with ST‐elevation myocardial infarction with timely reperfusion therapy: a pharmaco-invasive approach - Dasbiswas, Arup; Shelke, Abhijeet; Singhal, Anurag; Shah, Bhupesh (International Journal of Advances in Medicine, 2020)
The prevalence of cardiovascular diseases continues to increase in India, with a rapid epidemiological transition. Timely management of ST-elevation myocardial infarction (STEMI)is the key to decrease mortality and morbidity rates. In India, patients most often do not receive optimal therapy owing to a number of factors such as socio-economic constraints, lack of knowledge, geographical restrictions etc, leading to suboptimal outcomes. The timely delivery of optimal reperfusion strategy for STEMI patients is immensely challenging for physicians, due to several reasons. Primary percutaneous coronary Intervention (PCI) is still a global gold standard for the treatment of STEMI. Delayed case presentation is a significant challenge, especially in Indian tier towns/cities, because of prolonged transportation time or traffic delays with regards to reaching a PCI facility. Keeping in mind the accessibility to PCI facility because of geographical locations as well as affordability concerns especially in smaller Indian towns, pharmaco-invasive approach is almost as effective and a practical approach for reduction of morbidity and mortality rates. Timely establishment of reperfusion therapy is critical for improving myocardial salvage in patients with STEMI. There is an urgent need for developing strategies for efficient STEMI management, such as timely delivery of reperfusion therapy; reinforcement of health system and professionals, implementation of guideline-based interventions, streamlined insurance policy and greater emphasis on patient awareness for detection of symptoms. In addition to the timely reperfusion therapy and other standard care drugs, statins and potassium channel activators have demonstrated clinically significant improvements in the outcome of STEMI management.